Characterization of Induced Pluripotent Stem Cell-derived Human Serotonergic Neurons - Cao, Lining; Hu, Rui; Xu, Ting; Zhang, Zhen-Ning; Li, Weida; Lu, Jianfeng (Frontiers in Cellular Neuroscience, 2017)
In the brain, the serotonergic neurons located in the raphe nucleus are the unique resource of the neurotransmitter serotonin, which plays a pivotal role in the regulation of brain development and functions. Dysfunction of the serotonin system is present in many psychiatric disorders. Lack of in vitro functional human model limits the understanding of human central serotonergic system and its related diseases and clinical applications. Previously, we have developed a method generating human serotonergic neurons from induced pluripotent stem cells (iPSCs). In this study, we analyzed the features of these human iPSCs-derived serotonergic neurons both in vitro and in vivo. We found that these human serotonergic neurons are sensitive to the selective neurotoxin 5,7-Dihydroxytryptamine (5,7-DHT) in vitro. After being transplanted into newborn mice, the cells not only expressed their typical molecular markers, but also showed the migration and projection to the host’s cerebellum, hindbrain and spinal cord. The data demonstrate that these human iPSCs-derived neurons exhibit the typical features as the serotonergic neurons in the brain, which provides a solid foundation for studying on human serotonin system and its related disorders.